Internet-Based Acceptance and Commitment Therapy: A Transdiagnostic Systematic Review and Meta-Analysis for Mental Health Outcomes. Issue 2 (March 2021) - Thompson, Emma M.; Destree, Louise; Albertella, Lucy; Fontenelle, Leonardo F.
Abstract: Internet-based acceptance and commitment therapy (iACT) primarily targets the process of psychological flexibility. Its accessibility and low-intensity delivery are applicable across different treatment and prevention scenarios. This transdiagnostic meta-analysis reviews the effectiveness of iACT on anxiety, depression, quality of life, and psychological flexibility across individuals with different psychological and somatic conditions/complaints, or undiagnosed complaints. Seven databases were searched for randomized controlled trials that reported on anxiety, depression, quality of life, and psychological flexibility outcomes from iACT in any adult population. Engagement with iACT was summarized and methodological and population-related variables were investigated as potential moderators of effectiveness. Across 25 studies, small pooled effects were found for all outcomes at post-assessment and maintained at follow-up time-points. Interventions with therapist guidance demonstrated greater effectiveness in improving depression and psychological flexibility outcomes compared to nonguided iACT, and populations defined by a psychological condition or symptoms (e.g., depressed samples) demonstrated greater improvements in anxiety compared to nonclinical or somatic populations (e.g., chronic pain samples or students). Participants completed on average 75.77% of iACT treatments. While we found iACT to be effective in improving and maintaining mental health outcomes across diverse populations, there was limited evidence of reliable, clinically significant effects. PROSPERO registration number: CRD42020140086. Highlights: We found small effects of iACT on all mental health outcomes The effects of iACT were maintained after active treatment periods All population types benefited from iACT in mental health outcomes Guided iACT may be more beneficial in improving some mental health outcomes Participants completed on average 75.77% of iACT treatments